Geology of the Arera-Vedra Valley mining area (Gorno district, Orobic Alps, Italy) - Luca Summino; Giulia Domenighini; Michele Giorno; Luca Barale; Carlo Bertok; Luca Martire; Nicolò Luigi Fiori; Emanuele Schivo; Fabrizio Piana (Journal of Maps)
The 1:10,000 geological map of the Arera-Vedra Valley area covers an area of about 12 km2 in the Orobic Alps (Lombardy, N Italy), and is accompanied by five underground maps corresponding to different levels of historic mining works. The area is characterized by a Triassic stratigraphic succession that hosts one of the most important Zn-Pb mining districts in Italy (Gorno district). Original surface and underground geological mappings have been integrated with the analysis of drillhole stratigraphies and historic underground geological maps. Detailed geological cross sections correlating surface map data with those of the underground mining tunnels have been done. This work proposes a new map representation that is consistent with new interpretation of the geometry of the orebodies at depth, to serve as a tool for mining purposes (targets definition, mine design) and for a better understanding of the genesis of the Gorno ‘Alpine-type’ deposits.